The last temptation of Christ [videorecording (DVD)] - Scorsese, Martin; Dafoe, Willem; Keitel, Harvey; Hershey, Barbara, 1948-; Kazantzakis, Nikos, 1883-1957 (Criterion collection ;, 2000)
In this controversial movie, Jesus, as both fully human and fully divine, is viewed as free of sin but subject to all temptations, including sexual ones.